Testing the possibility of producing chemical injection in the walls of calcareous stones and in the lime mortars - Trochonowicz, Maciej (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The obtained positive results of calcareous stone and lime mortar hydrophobisation allowed to expand the scope of research. It was decided to conduct a membrane trial implementation by injection in the walls. Because of the difficulty in field tests it was decided to elevated walls in the laboratory. After a period of aging three variants of chemical membranes was performed in the three research walls. For injection was used the preparation selected in the first step of tests. The next stage of work was verifying the effectiveness of made membranes.